The Influence of the Motor Traction Vibration on Fatigue Life of the Bogie Frame of the Metro Vehicle - Qiushi Wang; Jinsong Zhou; Dao Gong; Tengfei Wang; Jiangxue Chen; Taiwen You; Zhanfei Zhang (Shock and Vibration)
During the service life of metro vehicles, the cracks frequently appear at the root of motor seats. This indicates the previous antifatigue designs are unable to cover the actual operating environment. Some individual loads, such as motor vibration, have been ignored or wrongly understood, which leads to the occurrence of local insufficient fatigue life of the frame. To illustrate the influence of the motor vibration on the fatigue life of the bogie frame, a metro vehicle was taken as an example: first, the precise finite element model of the frame was established, and its correctness was verified; then, the vibration characteristics of the frame were analyzed by sweep frequency calculation; and finally, considering the vibration acceleration signal of the motor measured on a metro line as the excitation, the influence of the random vibration on the fatigue life of the frame under traction and idle running conditions was compared and analyzed by solving the power spectral density of the dynamic stress response at the weak fatigue nodes of the structure. The results show that the energy of the vibration in the frame is mainly concentrated in modes 6 and 7, which are excited by the motor transverse and vertical vibration, respectively, and contribute a lot to the fatigue damage of the frame; the fatigue life of the vital positions of the frame under the traction condition significantly reduces compared to the idle running condition; and the contribution of the low-amplitude vibration above 300 Hz to the fatigue damage can be ignored. At last, the importance of the influence of the motor traction vibration on the fatigue life should be fully considered in the metro vehicle design was proposed.